PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KECAMATAN SETU KOTA TANGERANG SELATAN - Tri Andini; Syawaludin (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine how leadership style and work discipline influence employee performance at Setu District, South Tangerang City. It also seeks to understand the effect of leadership style on employee performance and the effect of work discipline on employee performance in Setu District, South Tangerang City. The method used in this research is quantitative, with data collection techniques through questionnaires distributed to 79 employees of Setu District, using saturated sampling. Data analysis includes validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, simple and multiple linear regression, correlation coefficient tests, coefficient of determination tests, and significance tests of the F-test. The results show that simultaneously, leadership style and work discipline have a positive and significant effect on employee performance, as indicated by the F-test result with Fhitung = 527.221 and sig. = 0.000 < 0.05. The multiple linear regression equation obtained is Y = -0.224 + 0.678 X1 + 0.303 X2. The correlation coefficient R is 0.966, indicating a very strong multiple relationship between the two independent variables and the dependent variable. The coefficient of determination R Square shows that 0.933 or 93.3% of employee performance variables are collectively influenced by leadership style and work discipline.